2020
DOI: 10.1016/j.heliyon.2020.e04007
|View full text |Cite
|
Sign up to set email alerts
|

3-Year effect of weight loss via severe versus moderate energy restriction on body composition among postmenopausal women with obesity - the TEMPO Diet Trial

Abstract: We have previously shown that a severely energy-restricted diet leads to greater loss of weight, fat, lean mass and bone mineral density (BMD) at 12 months in postmenopausal women with obesity than a moderately energyrestricted diet. We now aim to evaluate whether these effects are sustained longer term (ie, at 36 months). 101 postmenopausal women were randomized to either 12 months of moderate (25 to 35%) energy restriction with a food-based diet (moderate intervention), or 4 months of severe (65 to 75%) ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Weight cycling, which is repeated bouts of intentional weight loss followed by weight regain, has not been shown to cause measurable psychological harm in individuals with obesity who seek weight loss treatment—rather weight cycling is thought to be a result of pre-existing psychological factors [ 51 , 52 , 53 , 54 ]. Contrary to the popular perception among HCPs, weight regain is not related to the severity of dietary energy restriction [ 26 ]. Formal education and training may be a way to improve this misconception among HCPs.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Weight cycling, which is repeated bouts of intentional weight loss followed by weight regain, has not been shown to cause measurable psychological harm in individuals with obesity who seek weight loss treatment—rather weight cycling is thought to be a result of pre-existing psychological factors [ 51 , 52 , 53 , 54 ]. Contrary to the popular perception among HCPs, weight regain is not related to the severity of dietary energy restriction [ 26 ]. Formal education and training may be a way to improve this misconception among HCPs.…”
Section: Discussionmentioning
confidence: 80%
“…Another barrier to MRP prescription was the perception of poor long-term weight loss maintenance, with 49% of HCPs reporting that weight loss achieved during a meal replacement diet was not durable. In comparison to hypo-energetic food-based dietary interventions, severely energy-restricted meal replacement diets are more effective at weight loss and weight loss maintenance [ 26 , 43 ]. One long-term clinical trial demonstrated that at 3 years, after 4 months of severely energy-restricted meal replacement diet, 7.3 kg weight loss was maintained long-term.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations